Constitutive expression of c-fos and c-jun, overexpression of ets-2, and reduced expression of metastasis suppressor gene nm23-H1 in rheumatoid arthritis. - Dooley, S (1996)
OBJECTIVES: To identify genes that are involved in the development and progression of rheumatoid arthritis (RA). METHODS: We used a multiple gene analysis system and a set of available genes participating in processes such as proliferation, differentiation, tumour progression, and metastasis, to identify their RA related expression. Synovial tissues from 22 patients with RA were evaluated in comparison with those from six patients with osteoarthritis and two patients with non-inflamed joints as controls, using northern blot and reverse transcriptase polymerase chain reaction experiments. RESULTS: Our data confirm the role of c-fos and c-jun as constitutive signal transmitters in solid RA tissues, thus demonstrating the potential of the approach. Activation of both genes persisted through multiple passages of the cells in tissue cultures derived from the synovial lining of RA tissues. There was an increased expression of ets-2 in 30% of RA samples and an up to 30-fold decreased expression of the potential metastasis suppressor gene nm23-H1 in 90% of RA tissues, compared with control tissues. CONCLUSIONS: The data presented show for the first time a significant decrease of nm23-H1 expression in RA, which is possibly involved in local invasiveness, and a strong activation of the ets-2 nuclear oncogene in about one third of RA tissues, which may also be part of a pathway leading to advanced disease stages. The constitutive expression of c-fos and c-jun in RA tissue most probably results from a continuing inflammatory stimulus. These findings with cell cultures suggest an intrinsic activation mechanism of these early response genes in RA.